Changes in Feeding Behavior and Feeding Stress Among Mothers of Preschoolers Before and During the Novel Coronavirus Pandemic - Mosli, Rana H.; Barahim, Alaa; Zahed, Lina A.; Ishaq, Sara A.; Al-Eryani, Fatimah M.; Alharbi, Warda A.; Kutbi, Hebah A.; Saleemani, Haneen (Frontiers in Nutrition, 2022)
Objective: To examine changes in maternal feeding behaviors (MFB) and maternal feeding stress (MFS) among mothers of preschoolers in Saudi Arabia before and during the novel coronavirus pandemic. Methods: This is a prospective cohort study including 64 mothers of preschoolers who were drawn from a sample of a 2019 study. Study questionnaire was completed during November-December 2020. MFB were assessed using the Child Feeding Questionnaire-Arabic (CFQ-A) and MFS was assessed using the MFS-mealtimes index and the MFS-maternal resentment/difficult child index. Paired samples t-tests were used to examine changes in MFB and MFS. Results: Mothers have reported an increase in perceived responsibility (M= 4.09, SD= 0.87 vs. M= 4.33, SD= 0.59, P-value<0.05) and monitoring (M=4.23, SD=0.73 vs. M= 4.48, SD=0.66, P-value<0.05) during the pandemic period compared to the period prior to the pandemic. Mothers have reported a decrease in use of food as a reward (M=4.11, SD= 0.87 vs. M=2.30, SD=0.88, P-value<0.001) and concern about child’s diet (M=3.34, SD= 1.12 vs. M= 2.55, SD=1.04, P-value <0.001). There was an increase in MFS-maternal resentment/difficult child (M=2.47, SD=0.68 vs. M=2.71, SD=0.72, P-value<0.01). Conclusions: Findings can help inform future research aiming to measure the long-term effects of the pandemic on child outcomes.